2005
DOI: 10.1103/physreve.71.016222
|View full text |Cite
|
Sign up to set email alerts
|

Delayed feedback control of chaos: Bifurcation analysis

Abstract: We study the effect of time delayed feedback control in the form proposed by Pyragas on deterministic chaos in the Rössler system. We reveal the general bifurcation diagram in the parameter plane of time delay τ and feedback strength K which allows one to explain the phenomena that have been discovered in some previous works. We show that the bifurcation diagram has essentially a multi-leaf structure that constitutes multistability: the larger the τ , the larger the number of attractors that can coexist in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…Thus, the control scheme does not rely on a reference system and has only a small number of control parameters, i.e., the feedback gain K and time delay τ . It has been shown that TDAS can stabilize both unstable periodic orbits, e.g., embedded in a strange attractor [4,5], and unstable steady states [6,7,8]. In the first case, TDAS is most efficient if τ corresponds to an integer multiple of the minimal period of the orbit.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the control scheme does not rely on a reference system and has only a small number of control parameters, i.e., the feedback gain K and time delay τ . It has been shown that TDAS can stabilize both unstable periodic orbits, e.g., embedded in a strange attractor [4,5], and unstable steady states [6,7,8]. In the first case, TDAS is most efficient if τ corresponds to an integer multiple of the minimal period of the orbit.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that time-delayed feedback may not only be used for controlling a system but also for creating new dynamics is not new. Nevertheless, the investigation of delay-induced bifurcations and multistability is still a growing field [Balanov et al, 2005;Xu & Yu, 2004] with applications to the logistic map as well as to laser equations [Martínez-Zérega & Pisarchik, 2005;Martínez-Zérega et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Unstable periodic orbits with periods T 1 ≈ 5.91679 ("period-1 orbit") and T 2 ≈ 11.82814 ("period-2 orbit") are embedded in the chaotic attractor. As shown in [Balanov et al, 2005] by a bifurcation analysis, application of TDFC with τ = T 1 and 0.24 < K < 2.3 stabilizes the period-1 orbit, and it becomes the only attractor of the system. In [Just et al, 1997] it was predicted analytically by a linear expansion that control using the standard TDFC can only be realized in a finite range of the values of K : At the lower control boundary the limit cycle undergoes a period-doubling bifurcation, and at the upper boundary a Hopf bifurcation occurs generating a stable or an unstable torus from a limit cycle (Neimark-Sacker bifurcation).…”
Section: Stabilization Of An Unstable Periodic Orbit In the Rössler Smentioning
confidence: 99%